THE EFFECT OF FREE CASH FLOW AND LEVERAGE ON STOCK PRICES WITH DIVIDEND POLICY AS AN INTERVENING VARIABLE: PENGARUH FREE CASH FLOW DAN LEVERAGE TERHADAP HARGA SAHAM DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL INTERVENING - Nur Rohmatika; Ati Sumiati; Mardi Mardi (Yayasan Education and Social Center, 2022)
This study aims to determine whether there is an effect of free cash flow and leverage (debt equity ratio) on stock prices through dividend payout ratios at the Kompas 100 Index non-banking companies listed on the Indonesia Stock Exchange in 2019. Free cash flow used free cash flow calculated. Leverage used debt to equity ratio (DER), Dividend policy used dividend payout ratio (DPR) based on profit for year 2019 and stock price used closing price in 2020. The data analysis technique used in this research is regression analysis, path analysis, and Sobel test, multiple correlation test, coefficient of determination test, t test, and f test. Data analysis used IBM SPSS Statistics 26. The results: (1) free cash flow had a significant positive effect on dividend policy. (2) leverage has a significant negative effect on dividend policy. (3) free cash flow has a direct and not significant positive effect on stock prices. (4) leverage has a direct and insignificant negative effect on stock prices, (5) dividend policy has a significant positive effect on stock prices. (6) dividend policy is able to mediate free cash flow on stock prices positively and not significantly. (7) dividend policy is not able to mediate the effect of leverage on stock prices